LOCATION QUOTIENT DAN SIFT SHARE PRODUK DOMESTIK REGIONAL BRUTO - Dyah Ayu Retno Inten (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
Sleman Regency is one of the regencies in the Special Region of Yogyakarta Province which has a GRDP that is in line with the GRDP of the Special Region of Yogyakarta Province. To measure economic performance and its impact on the growth of the Special Region of Yogyakarta Province, calculations are needed using the LQ method and the shift share method. This study uses secondary data in the form of GRDP data for Sleman Regency and the Special Region of Yogyakarta Province in 17 business sectors in 2018-2023. The results show that there are 7 basic sectors, namely 1) Manufacturing Industry, 2) Construction, 3) Provision of Accommodation and Food and Beverage, 4) Real Estate, 5) Company Services, 6) Education Services, 7) Health Services and Social Activities. Furthermore, based on the results of the shift share analysis, Sleman Regency has 6 priority leading sectors, namely 1) Electricity & gas procurement, 2) Information and communication, 3) Financial Services & insurance, 4) Education Services, 5) Health Services and Social Activities, 6) Other services